# Find the Y-Intercept 7x-9y=-15 7x-9y=-15
Rewrite in slope-intercept form.
The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.
y=mx+b
Subtract 7x from both sides of the equation.
-9y=-15-7x
Divide each term by -9 and simplify.
Divide each term in -9y=-15-7x by -9.
-9y-9=-15-9+-7x-9
Cancel the common factor of -9.
Cancel the common factor.
-9y-9=-15-9+-7x-9
Divide y by 1.
y=-15-9+-7x-9
y=-15-9+-7x-9
Simplify -15-9+-7x-9.
Simplify each term.
Cancel the common factor of -15 and -9.
Factor -3 out of -15.
y=-3(5)-9+-7x-9
Cancel the common factors.
Factor -3 out of -9.
y=-3⋅5-3⋅3+-7x-9
Cancel the common factor.
y=-3⋅5-3⋅3+-7x-9
Rewrite the expression.
y=53+-7x-9
y=53+-7x-9
y=53+-7x-9
Dividing two negative values results in a positive value.
y=53+7×9
y=53+7×9
Reorder 53 and 7×9.
y=7×9+53
y=7×9+53
y=7×9+53
Rewrite in slope-intercept form.
y=79x+53
y=79x+53
Using the slope-intercept form, the y-intercept is 53.
b=53
Find the Y-Intercept 7x-9y=-15   ## Download our App from the store

### Create a High Performed UI/UX Design from a Silicon Valley.  Scroll to top